Pengembangan Objek Wisata Pantai Bandar Mutiara Oleh Pemerintah Kabupaten Agam - Mulya; Ariany, Ria (STIA Bina Banua Banjarmasin, 2024)
Tourist attraction development is an activity to build, maintain, and preserve parks, facilities, and infrastructure, as well as other facilities. The legal basis for tourism development, which is in accordance with development principles, is Republic of Indonesia Law Number 10 of 2009 concerning tourism. The aim of this research is to determine the development of the Bandar Mutiara Beach tourist attraction by the Agam Regency government. The method used is a descriptive method with a qualitative approach. The theory used is the opinion of George R. Terry which consists of four indicators of good management, namely Planning, Organizing, Actuacting, and Controlling. Informants used observation, interview and survey techniques to the Head of the Youth and Sports Tourism Department, Head of the Tourism Promotion Division, Head of the Tourism Destination Division, Tourist Attraction Officers, the community regarding the development of the Bandar Mutiara tourist attraction. The results obtained are that based on the results of the evaluation and monitoring, strong leadership and a long-term perspective from the local government and other stakeholders have a crucial role in providing direction, motivation and support needed to achieve the goals of developing the pearl bandar tourist attraction, improvements or adjustments can be made. future development strategies that are fair to local communities. The active role of local communities is an important aspect that can strengthen the sense of ownership in the development of the Bandar Pearl tourist attraction.